Queue Tree Implementation for Bandwidth Management in Modern Campus Network Architecture - Liantoni, Febri; Perwira, Rifki Indra (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Bandwidth management in an institution becomes a fundamental need that must be managed properly. The continuous increase in the number of user, data and hardware technologies result in unequal distribution and bandwidth absorption. The increasingly diverse needs of the users in the virtual world require refined setting of bandwidth scheme. If bandwidth is not set properly, bandwidth can be accessed by multiple users. Institutions engaged in education consist of several parties such as employees, teachers and students (called student body). Queue implementation is a technique of dividing bandwidth according to the proportional needs of its users; moreover, this technique is able to work flexibly to organize and allocate bandwidth to end users. The ease of adding and reducing the amount of bandwidth becomes its main feature. The concept of campus network adopted from a Cisco fundamental system can serve as one model that can optimize the infrastructure and the distribution of bandwidth to end users. The method used in this research is employing direct observation, conducting interviews for problem identification and assigning the Internet service requirement and the availability of hardware and software resources. The optimization of bandwidth management by considering student body becomes the main objective. The implementation of queue on each network allows the distribution of bandwidth conforming the user satisfaction. Based on user satisfaction survey result, the user satisfaction level of Queue Tree implementation reached 59.2%.